Strategi Analisis Kelayakan Pengadaan Mesin Rotary Veneer Guna Meminimalkan Biaya produksi - Pradana, Arsandi Alfa; Lokajaya, I Nyoman (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Company PT. Romi Violeta experienced a problem, namely high production costs due to the use of cutting machines for Veneer using outside services. Based on the NPV method calculation, it produces Rp. 278.411.141. Calculations using the IRR method produce 14.67%. Calculations using BEP produce 3 years 6 months. Calculations using the B/C method produce 1.01. Calculations using the DBD Depreciation method produce a total of Rp. 1,785,251,635. It is said that by using the above method it is worth investing in a rotary veneer machine